2016
DOI: 10.11114/smc.v4i2.1952
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Identity in the Workplace and Affinity Group Spaces

Abstract: The following paper examined affinity group creation and purpose through an identity management lens by addressing the utility of an affinity group for those currently involved in homogeneous racial and nonracial groups as well as larger organizational diversity sessions. A thematic analysis revealed affinity group perceptions including several subthemes (logistics, helpful, harmful, more heterogeneity, and exclusion of identity). Organizational diversity sessions at large revealed similar subthemes (legitimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The Mercer report [24] identified at least three specific ways in which AGs serve D&I strategies including: 1) serve as focus groups to provide feedback for D&I strategists, 2) implement specific strategies, such as mentoring and onboarding, and 3) act as agents of cultural change in the organization. Furthermore, attribute-centered AGs, such as WAGs, legitimize marginalized identities by raising awareness, creating a safe space for emotional support to negotiate identity through communication, and providing a platform to advocate for equity [23].…”
Section: What Are Affinity Groups (Ags)?mentioning
confidence: 99%
See 4 more Smart Citations
“…The Mercer report [24] identified at least three specific ways in which AGs serve D&I strategies including: 1) serve as focus groups to provide feedback for D&I strategists, 2) implement specific strategies, such as mentoring and onboarding, and 3) act as agents of cultural change in the organization. Furthermore, attribute-centered AGs, such as WAGs, legitimize marginalized identities by raising awareness, creating a safe space for emotional support to negotiate identity through communication, and providing a platform to advocate for equity [23].…”
Section: What Are Affinity Groups (Ags)?mentioning
confidence: 99%
“…Our assessment of WAG characteristics revealed that these groups provide great benefits for their members. However, in their current state, WAGs are not currently positioned to address the barriers inherent in the power structures that privilege interests and experiences of the dominant culture that simultaneously silence or ignore marginalized IT women [23], [26]. Therefore our investigation of WAGs must be theoretically based and grounded in critical epistemology that will uncover these power dynamics and give voice to marginalized groups [23], [37].…”
Section: A Need For Theoretically Grounded Critical Research On Wagsmentioning
confidence: 99%
See 3 more Smart Citations